(untitled) (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2025)
ABSTRACT Introduction: Participation in sports competitions over time is associated with significant improvements in performance and athletic ability. Objective: To determine the relationship between competitive experience and athletic talent in elite taekwondo athletes. Methodology: A quantitative study was conducted, with a quasi-experimental observational design and a descriptive-correlational scope. This study was conducted with elite taekwondo athletes participating in sports camps affiliated with the national Taekwondo organization in the United States (USAT) during the year 2023. Competitive experience was considered as the number of sports competitions participated in throughout the athlete’s career. Athletic talent, on the other hand, was measured as the position in the USAT national ranking. Results: After conducting a Pearson correlation analysis of the key variables in this study, a statistically significant inverse correlation was found between competitive experience and athletic talent (p>0.000). This suggests that greater competitive experience (higher number of competition participations) is related to a lower position (closer to the 1st position) in the USAT ranking. Conclusion: In conclusion, a statistically significant relationship was found between competitive experience and athletic talent. The evidence suggests that greater experience in competitions contributes to competitive success and a higher level of technical skill in this discipline. Through participation in competitions, taekwondo athletes could receive direct feedback on their performance, allowing them to adjust and improve their skills.